Cu(II) and Ni(II) Complexes of Bidentate E-N-(4-Isopropyl benzylidene)isonicotinohydrazide: Synthesis, Characterization, DNA Cleavage and Antioxidant Activity - Geetha, R.; Rajasekar, K.; Balasubramaniyan, S.; Selvarani, R.; Veeravel, C. (Asian Journal of Chemistry, 2022)
The reaction of Cu(NO3)2·3H2O and Ni(NO3)2·6H2O with E-N-(4-isopropylbenzylidine)isonicotinohydrazide derived from isonicotinic acid hydrazide with 4-isopropyl benzaldehyde were synthesized and characterized structurally by physico-chemical and spectral techniques. The metal-ligand ratio in metal complexes is in the order of metal:ligand1:ligand2 (1:1:1) indicating the formulae of the complexes as [M(SB)2(NO2)2] (where M = Cu2+ & Ni2+, SB = C16H17N3O). The magnetic moment and electronic spectral data suggest tetragonal geometry for Cu(II) complex and octahedral geometry for Ni(II) complex around the central metal ions. The FT-IR and Far-IR spectroscopic data suggest the bidentate nature of ligand. The geometry of the Cu(II) complex and its covalence is confirmed by EPR spectral data. The Thermal decomposition of metal complexes has been identified using thermogravimetric analysis. The conductometric measurements proved the non-electrolytic behaviour of all the compounds. With the help of the agarose gel electrophoresis method, the DNA cleavage studies of Schiff base metal complexes were predicted. Also, the in-vitro antioxidant activity of Cu(II) complex was determined by a free radical scavenging assay.